DEVELOPMENT OF MULTIMEDIA ON DRESSING SKILL FOR SKILLS FOR STUEDENT WITH AUTISM - Sripunchat, Charoenkhwan (Journal of Education and Innovation, 2025)
The objectives of this research were: 1) to develop the multimedia on dressing skills for students with autism, and 2) to study the effect of multimedia usage on dressing skills for students with autism. The target group consisted of 3 students with autism with their age ranged between 6-7 years old. The design of this research was Research and Development including the experiment and case study. The research instruments included: 1) Three Multimedia titled “Dressing Practice with Paper, Ida inviting to practice one’s skirt and pant, and Omsin can wear socks and shoes by oneself, and 2) Nine Activity Management Plans of multimedia usage on dressing skills for students with autism, 3) The Evaluation Form of Dressing Skills.” The instruments were Value. 4) Multimedia quality assessment form. Bring research tools to experts. By evaluating content, language, sound, and screen design. Including the consistency of the assessment form, Each item’s IOC value is between 0.67 - 1, with values greater than 0.5 considered consistent. The quality of the multimedia scored 80. The instruments being evaluated by experts were developed for 4 weeks Monday, Wednesday and Friday from 12.00 – 12.30 pm. Then, they were used for practicing on dressing skills for students with autism during 4 weeks. Post-test data were recorded every hour. The findings of multimedia usage were colluded every hour. Data were analyzed and presented using basic statistics, including Percentages, and Descriptive statistics. The research found that: 1. The IOC Mean Value of Multimedia titled Dressing Skills of Students with Autism Each item’s IOC value is between 0.67 - 1, with values greater than 0.5 considered consistent. The quality of the Multimedia Scores was 80 or higher. It was found that the Multimedia could effectively be used for developing dressing skills in students with autism. 2. The findings of Multimedia usage titled Dressing Skills of Students with Autism found that three students’ posttest scores were higher than the pretest scores in all of 3 stories. The first student showed increased score 87.00%. The second student showed increased score 19.17%. The third student showed increased score for 42.22%. Therefore, the usage of Multimedia titled Dressing Skills of Students with Autism was increased in every student.